Function Identification of the Nucleotides in Key cis-Element of DYSFUNCTIONAL TAPETUM1 (DYT1) Promoter - Zhou, Shumin; Zhang, Hongli; Li, Ruisha; Hong, Qiang; Li, Yang; Xia, Qunfang; Zhang, Wei (Frontiers in Plant Science, 2017)
As a core regulatory gene of the anther development, DYSFUNCTIONAL TAPETUM1 (DYT1) was expressed in tapetum preferentially. Previous study had confirmed that a ‘CTCC’ sequence within DYT1 promoter was indispensable for correct DYT1 expression. However, precise analysis on the function of each nucleotide of this sequence still lacks. Here we employed site mutation assay to identify the function roles of the nucleotides. As a result, the ‘T’ and final ‘C’ of ‘CTCC’ were found essential for the temporal and spatial specificity of DYT1expression, whereas the other two ‘C’ nucleotides exhibited substitutable somewhat. The substitutes of two flanking nucleotides of ‘CTCC’, however, hardly affected the normal promoter function, suggesting that the ‘CTCC’ sequence as a whole did meet the standard of a canonical cis-element by definition. In addition, it was found that as short as 497bp DYT1 promoter was sufficient for tissue-specific expression, while longer 505bp DYT1 promoter sequence was sufficient for species-specific expression.